دراسة منهجية في اختلاف نظرة المفسرين للمصطلحات القرآنية = A systematic study of the different interpreters' perception of Qur'anic terms - Bugrein, Amna Mohamed; Elatrash, Radwan Jamal Yousef (IIUM Press, International Islamic University Malaysia, 2020)
بالرغم من كثرة الدراسات والبحوث في جانب دراسة الألفاظ القرآنية وتعريفاتها والفروق المعنوية ما بينهاإلا أننا نجد أنه أشكل على كثير من طلبة العلم الخلط بين المفاهيم القرآنية واستبدالها بالمترادفات وتجاهلوا السياق الذي انبثق منه ذلك المصطلح، وكذلك فإننا نجد ندرة في دراسة هذه المصطلحات القرآنية من جانب تأثير اختلاف معانيها في تفسيرات المفسرين القدامي والمعاصرين. والمدقق اللغوي والتفسيري يجد أن من أدوات التفسير الاهتمام بالمصطلح القرآني، ونشأعن هذا الاهتمام مجموعة كبيرة من التفاسير لكتاب الله تعالى، وفي هذا البحث سنحاول دراسة تفسير مجموعة من المفسرين لأربع كلمات قرآنية هي: التدبر، والتفكر، والتفسير، والتأويل. ولأن طبيعة البحث تعتمد الفروق المنهجية بين المفسرين اقتضتالمنهج الاستقرائي والتحليلي. ومن أهم النتائج التي توصل إليها البحث هي أن اختلافهم في بيان معاني الكلمات القرآنية(محلّ الدارسة)ليس له الأثر البين في اختلاف تفاسيرهم واختلاف تفاسيرهم لكتاب الله نتيجة اختلاف طرقهم ومناهجهم التفسيرية أو توجهاتهم المذهبية إلى غير ذلك من الأسباب. *************************************************************************** Qur’an has and is still the focal point of Islamic thoughts and scholarly efforts. Because of that, the interpretation of Qur’an (Tafsir) is one of most important Islamic disciplines. Muslim scholars undertook unwavering effort in interpreting every single letter in Qur’an which has produced a vast library of Tafasir in all Qur’anic subfields. This study aims to research the interpretations of four words in the Qur’an namely, Tadabbur, Tafakkur, Tafsir and Ta’wil to find the differences in interpretation between different scholars and to what extent this has affected their interpretation methodology of the whole Qur’an. Employing a qualitative deductive methodology, this study found that the interpretation of the aforementioned words does not have a significant influence on the scholar’s interpretation of the whole Qur’an. Rather, their interpretations are more influenced by their Mathahib, their chosen methodology and other factors